2023
DOI: 10.1039/d3dt02179c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cytotoxicity studies of Cu(i) and Ag(i) complexes based on sterically hindered β-diketonates with different degrees of fluorination

Maura Pellei,
Jo’ Del Gobbo,
Miriam Caviglia
et al.

Abstract: Design, synthesis, and in vitro antitumor properties of Cu(I) and Ag(I) phosphane complexes supported by the anions of sterically hindered β-diketone ligands, 1,3-dimesitylpropane-1,3-dione (HLMes), and 1,3-bis(3,5-bis(trifluoromethyl)phenyl)-3-hydroxyprop-2-en-1-one (HLCF3) featuring trifluoromethyl or...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 121 publications
0
5
0
Order By: Relevance
“…On the other hand, very few studies on the biological activity of group 11 metal complexes of β-diketones have been reported in the literature to date [44] and copper(I)-based anticancer complexes supported by β-diketonate ligands remain an unexplored research field. Recently, as part of our continuous investigation on the chemical and biological properties of coinage metal complexes [45][46][47][48][49][50][51], we reported the first study on the syntheses, characterization and biological evaluation of new Cu(I) complexes containing triorganophosphanes and the anion of several sterically hindered the β-diketone ligands [52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, very few studies on the biological activity of group 11 metal complexes of β-diketones have been reported in the literature to date [44] and copper(I)-based anticancer complexes supported by β-diketonate ligands remain an unexplored research field. Recently, as part of our continuous investigation on the chemical and biological properties of coinage metal complexes [45][46][47][48][49][50][51], we reported the first study on the syntheses, characterization and biological evaluation of new Cu(I) complexes containing triorganophosphanes and the anion of several sterically hindered the β-diketone ligands [52].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as an extension of our studies on pyrazolyl derivatives and as part of our continuous investigation on the chemical and biological properties of copper-containing coordination compounds [46][47][48][49]52,86], we report here for the first-time a study on the syntheses, characterization and reactivity of new 3-monosubstituted acetylacetone ligands, HL acPz and HL acPzMe (Scheme 2), and related Cu(II) and Cu(I) complexes containing phosphane co-ligands, that could be evaluated for their biological effects and for their catalytic activity and selectivity. In particular, these species may be considered as versatile coordinating ligands having two different donor sites of different Pearson hardness [87] (a soft neutral nitrogen atom of the pyrazolyl moiety and a hard oxygen donor atoms of the acetylacetone moiety).…”
Section: Introductionmentioning
confidence: 99%
“…For comparison reasons, the cytotoxicity of the reference metal-based chemotherapeutic drug cisplatin was assessed under the same experimental conditions. Cytotoxicity data for the corresponding uncoordinated ligands and their salts have been previously reported [88]. The cytotoxicity results showed that, except the iron derivatives 2, 8 and 14, all tested complexes demonstrated significant antiproliferative activity towards all cancer cell lines belonging to the in-house cancer cell panel, showing IC 50 values in the micromolar range.…”
Section: Biological Studiesmentioning
confidence: 76%
“…The ligand HL Ph was obtained from commercial sources and used as received. The ligands HL CF3 [86], HL Mes [87] and the related sodium salt NaL Mes [88] were prepared according to procedures detailed in the literature and were fully characterized. For comparison with the related metal complexes, we reported in the Supplementary Material the spectroscopic characterizations of the sodium salts NaL CF3 , NaL Mes and NaL Ph (FT-IR (Figures S4, S9 and S13), 1 H-NMR (Figures S5, S10 and S14), 13 C{ 1 H}-NMR (Figures S6, S11 and S15), 19 F{ 1 H}-NMR (Figure S7) and ESI-MS (+) (Figures S8, S12 and S16) spectra).…”
Section: Materials and General Methodsmentioning
confidence: 99%
See 1 more Smart Citation